Case report: A longitudinal study of an unusual rapidly progressive dementia case - Liu, Xiaoyan; Fan, Ziqi; Chen, Xuanyu; Zhang, Yanyan; He, Fangping; Ma, Xiaohua; Ke, Qing (Frontiers in Neurology, 2023)
It is daunting to determine the etiology of rapidly progressive dementia (RPD), which includes metabolic, neoplastic, infectious, autoimmune, neurodegenerative and other conditions. Herein, we illustrate an unusual case of a patient primarily exhibiting RPD, overlapping sleep dysfunction, psychosis and abnormal movement, which was finally defined as anti-IgLON5 disease, a novel and rare autoimmune encephalopathy. Furthermore, we longitudinally described his cognitive and psychological performance in detail, and determined that early initiation of immunotherapy in this patient did not result in a good outcome. These data highlight anti-IgLON5 disease as a possible differential diagnosis in patients with RPD.